التداول الخوارزمي وانعكاساته على الأسواق المالية العالمية - بن قراب, صفية (جامعة الوادي - University of Eloued, 2023)
تهدف هذه الدراسة إلى توضيح انعكاسات التداول الخوارزمي على الأسواق المالية العالمية، حيث يلجأ المستثمرون إلى استخدامه نظرا لأن له قدرة أفضل على الاستجابة بسرعة لظروف السوق المتغيرة، وقد تم الاستعانة بالمنهج التاريخي للعودة إلى الجذور تاريخية للتداول الخوارزمي والمنهجين الوصفي والتحليلي لوصف مختلف المفاهيم النظرية المتعلقة بمتغيرات الدراسة، وتحليل مدى تطور حجم استخدام التداول الخوارزمي وانعكاساته على الأسواق المالية العالمية في الجانب التطبيقي. وقد خلصت هذه الدراسة إلى أنه على الرغم من الآثار الإيجابية للتداول الخوارزمي، مثل مساهمته في زيادة سيولة السوق المالي وخفض تكاليف المعاملات. إلا أنه يحمل أيضا مخاطر قد تتطلب تدابير فعالة لتقليلها وتجنب خسائر كبيرة للمتداولين. This study aims to clarify the implications of algorithmic trading on the global financial markets, where investors resort to using it because it has a better ability to respond quickly to changing market conditions The historical approach was used to return to the historical roots of algorithmic trading and the descriptive and analytical approaches to describe the various theoretical concepts related to the variables of the study, and to analyze the extent of the development of the use of algorithmic trading and its repercussions on the global financial markets in the applied side. This study concluded that despite the positive effects of algorithmic trading, such as its contribution to increasing the liquidity of the financial market and reducing transaction costs. However, it also carries risks that may require effective measures to reduce them and avoid significant losses for traders.
Algorithmic trading and its implications for global financial markets
مقال
Keywords: أسواق مالية ; تداول خوارزمي ; تداول عالي تردد ; تداول كمي ; تداول آلي; financial markets, algorithmic trading, high frequency trading, quantitative trading, automated trading